Textbooks and Reading Materials. Volume Three Outcomes of the Regional Seminar. Report of a Regional Seminar on Textbooks and Reading Materials (Wellington, New Zealand, October 4-12, 1983). - New Zealand Dept. of Education, Wellington; New Zealand Dept. of Education, Wellington; United Nations Educational, Scientific, and Cultural Organization, Bangkok (Thailand). Regional Office for Education in Asia and the Pacific (Washington, D.C. : Distributed by ERIC Clearinghouse, 1984)
For the second of two volumes dealing with the effective use of instructional materials to teach reading, this booklet describes the participants and outcomes of a regional seminar on the use of reading instruction materials and textbooks held in New Zealand. The first section of the booklet provides an overview of the seminar, including objectives, participants and countries, and future actions proposed by participants. The second section considers major aspects of the development, provision, and use of textbooks and reading materials, including the functions of organizations and agencies; meeting needs for textbooks and reading materials; preparation, trial, and evaluation of textbooks; publication, production, and distribution of textbooks; textbook evaluation; cost reduction; and teacher involvement in the planning, preparation, trial, and evaluation of textbooks. Appended materials include summaries of the reports by New Zealand participants (specifically on the country's "Ready to Read" program, the publications branch of the New Zealand Department of Education, the project to revise and update the materials used in the reading program, and the teacher inservice program), a list of the seminar participants, the work schedule, and the opening address by New Zealand's Acting Minister of Education and Minister of Trade and Industry. (HTH)
ERIC Note: For Volume One, see CS 008 170.
Microfiche.
Keywords: Instructional Materials; International Relations; Reading Instruction; Reading Materials; Reading Programs; Seminars; Textbook Evaluation; Textbook Publication; Textbooks; New Zealand; Reports, Descriptive; Collected Works, Proceedings